Glycolysis in the tumor microenvironment: a driver of cancer progression and a promising therapeutic target - Zhao, Junpeng; Jin, Dandan; Huang, Mengxiang; Ji, Jie; Xu, Xuebing; Wang, Fei; Zhou, Lirong; Bao, Baijun; Jiang, Feng; Xu, Weisong; Lu, Xiaomin; Xiao, Mingbing (Frontiers in Cell and Developmental Biology, 2024)
Even with sufficient oxygen, tumor cells use glycolysis to obtain the energy and macromolecules they require to multiply, once thought to be a characteristic of tumor cells known as the "Warburg effect". In fact, throughout the process of carcinogenesis, immune cells and stromal cells, two major cellular constituents of the tumor microenvironment (TME), also undergo thorough metabolic reprogramming, which is typified by increased glycolysis. In this review, we provide a full-scale review of the glycolytic remodeling of several types of TME cells and show how these TME cells behave in the acidic milieu created by glucose shortage and lactate accumulation as a result of increased tumor glycolysis. Notably, we provide an overview of putative targets and inhibitors of glycolysis along with the viability of using glycolysis inhibitors in combination with